Ecuador : 2005 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Ecuador. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that despite a difficult political environment, economic growth in Ecuador is estimated to have exceeded 3 percent in 2005, with the non-oil sector expanding by 3 1\2 percent. The strong growth in the oil sector that followed the completion of the new oil pipeline in 2003 has tapered off, but high oil prices have helped bolster confidence and underpin domestic demand. The external current account deficit is estimated to have remained unchanged at about 1 percent of GDP.